Anti-interferon gamma treatment blocks the ability of glutaraldehyde- polymerized allergens to inhibit specific IgE responses (The Rockefeller University Press, 1991)
The lymphokines interleukin 4 and interferon gamma (IFN-gamma) have been shown to play an important role in regulation of polyclonal immunoglobulin E (IgE) and IgG2a responses in vitro and in vivo. We demonstrate here that treatment with chemically modified ovalbumin (OA) results in long-lived, 97-99% inhibition of allergen-specific murine IgE responses and 10(3)-10(4)-fold increases in anti-OA IgG2a. Responses to unrelated antigens are not affected. Treatment with unmodified OA under the same conditions fails to inhibit primary or secondary IgE responses or to increase IgG2a but does lead to pronounced increases in OA-specific IgG1 production. Glutaraldehyde- polymerized ovalbumin (OA-POL)-induced changes in IgE and IgG2a responses are abrogated by in vivo treatment with purified monoclonal anti-IFN-gamma antibody (XMG 1.2), a finding indicative of preferential IFN-gamma production upon exposure to chemically modified, but not native, allergen. The results suggest the possibility that the pattern of cytokine synthesis elicited after exposure to protein antigens, and the resulting immune response, may be dependent upon the form of antigen to which the individual is exposed and consequently may be subject to manipulation.